Integrating Islamic Values into Women’s Economic Roles: The Contribution of OJESY Drivers to Household Economy in Urban Indonesia - Unzhila Nur Ilmiatun P; Muslimin Kara; Ahmad Efendi (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study investigates the integration of Islamic values into the economic roles of women by focusing on Muslim women motorcycle taxi drivers (Ojek Syariah Muslimah or OJESY) in Indonesia. The objective is to examine the contribution of OJESY drivers’ income to household economies and the meanings associated with their work within an Islamic value framework. Using a phenomenological approach, data were collected through in-depth interviews and analyzed narratively to explore drivers’ motivations, income management strategies, and the balance between domestic and public roles. The findings indicate that OJESY drivers make significant contributions to household welfare by financing children’s education, increasing savings, and improving household assets. Participants perceive their work as morally safe and sharia-compliant, which fosters a sense of tranquility and strengthens social legitimacy. Despite these benefits, challenges remain, including income instability, the dual burden of work and family responsibilities, and limited access to social protection. The study recommends enhancing community-based support, expanding sharia-compliant entrepreneurial training, and integrating social protection mechanisms for informal workers on digital platforms. By framing OJESY within the context of maqasid al-sharia, particularly in preserving family welfare, the study contributes to the discourse on gender-inclusive Islamic economics and proposes policy innovations for sustainable and inclusive economic empowerment.